New training horizons: A MOOC experience as a resource in continuing education - Alicia Benet Gil; Aida Sanahuja Ribés; Irene García Molina; Raquel Nieto Garoz (Universidad de Guadalajara, 2018)
Since the current incorporation of the E-learning in the educational world, this study presents the design and evaluation of the MOOC (Massive Online Open Courses) called "El aula inclusiva hoy en día. Cómo afrontar el trastorno del espectro autista y las altas capacidades intelectuales" [The inclusive classroom today. How to deal with autism spectrum disorder and the high intellectual capabilities]. The aim of this study is to provide educational professionals with a more accessible and flexible training resource so that they can expand and reinforce knowledge. Thus, the main purpose is to know the participants' perceptions about the MOOC. A questionnaire ad hoc was used as a data collection instrument. Initially, 330 participants were enrolled in the course, of which 110 participants completed it satisfactorily and responded to the final evaluative questionnaire. Most of the subjects answered in a positive way to the totality of the questions, being generally satisfied in: topic, content, methodology and participation. The main contribution of this work lies in the potential of these courses as an accessible tool that allows the permanent training of the professionals of the education. As a proposal for improvement, the participants clarify to increase the number of time to perform the tasks. In conclusion, we can say that the MOOC is perceived as a satisfactory tool. This helps us to continue advancing in the field of online and distance learning, considering the MOOC as a powerful tool that provides a valuable channel for the exchange of content and knowledge by students from all over the world.